Novel homozygous mutation (c.175delG) in platelet glycoprotein ITGA2B gene as cause of Glanzmann's thrombasthenia type I - Vannier, Corinne; Behnisch, Wolfgang; Bartsch, I.; Sandrock, K.; Ertle, Florian; Schmidt, K.; Busse, A.; Superti-Furga, A.; Kulozik, Andreas; Santoso, S.; Zieger, Barbara (Klinische Pädiatrie, 2010)
Glanzmann's thrombasthenia (GT), is a rare autosomal recessive bleeding disorder. Platelets from patients with GT show quantitative or qualitative defects of the platelet membrane glycoprotein (GP) IIb/IIIa complex. A variety of genetic defects in ITGA2B and ITGB3 (genes for GPIIb and GPIIIa) has been described causing the clinical entity of GT.